The uncomfortable pew : Christianity and the new left in Toronto - Douville, Bruce, 1969- (McGill-Queen's University Press, 2021)
"In The Uncomfortable Pew, Bruce Douville explores the relationship between Christianity and the New Left in English Canada from 1959 to 1975. Focusing primarily on Toronto, he examines the impact that left-wing student radicalism had on Canada's largest Christian denominations, and the role that Christianity played in shaping Canada's New Left. Based on extensive archival research and oral interviews, this study reconstructs the social and intellectual world of young radicals who saw themselves as part of both the church and the revolution. Douville looks at major communities of faith and action, including the Student Christian Movement, Kairos, and the Latin American Working Group, and explains what made these and other groups effective incubators for left-wing student activism. He also sheds light on Canada's Roman Catholic, Anglican, and United churches and the ways that progressive older Christians engaged with radical youth and the issues that concerned them, including the Vietnam War, and anti-imperialism around the globe, women's liberation, and gay liberation. Challenging the idea that the New Left was atheistic and secular, The Uncomfortable Pew reveals that many young activists began their careers in student Christian organizations, and these religious and social movements deeply influenced each other. While the era was one of crisis and decline for leading Canadian churches, Douville shows how Christianity retained an important measure of influence during a period of radical social change."-- Provided by publisher.
Keywords: Christians -- Political activity -- Ontario -- Toronto -- History -- 20th century.; Youth -- Political activity -- Ontario -- Toronto -- History -- 20th century.; Radicalism -- Ontario -- Toronto -- History -- 20th century.; Right and left (Political science) -- Ontario -- Toronto -- History -- 20th century.; Social movements -- Ontario -- Toronto -- History -- 20th century.; Toronto (Ont.) -- Church history -- 20th century.; Chrétiens -- Activité politique -- Ontario -- Toronto -- Histoire -- 20e siècle.; Jeunesse -- Activité politique -- Ontario -- Toronto -- Histoire -- 20e siècle.; Radicalisme -- Ontario -- Toronto -- Histoire -- 20e siècle.; Mouvements sociaux -- Ontario -- Toronto -- Histoire -- 20e siècle.; RELIGION / Christianity / History.; Christians -- Political activity; Radicalism; Right and left (Political science); Social movements; Youth -- Political activity; Ontario -- Toronto; 1900-1999; Canada; Christianity; Christians--Political activity; General; History; New Left; Ontario--Toronto; Religion; Youth--Political activity; Church history